GENOTOXICITY EVALUATION OF CISSUS LATIFOLIA LAM. AND ITS GENOPROTECTIVE EFFECT ON OXIDATIVE DAMAGE INDUCED BY HYDROGEN PEROXIDE - M, RUBEENA; E THOPPIL, JOHN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study focused on the genotoxic efficacy of higher concentrations of methanolic extract of Cissus latifolia Lam. and its genoprotective role at lower concentrations against the induced cytogenetic aberrations by 2% hydrogen peroxide [H2O2] on the Allium cepa plant model. Methods: Cytotoxic and genoprotective potential of the plant extract were analyzed using A. cepa assay. The treatment modes that were designed for antigenotoxicity screening were pre-treatment, post-treatment, and concurrent treatment. Results: Results revealed the toxic effect of extract of C. latifolia which induced major chromosomal abnormalities, namely, nuclear lesions, chromosome vagrants, stickiness, bridges, and chromosome breaks. These aberrations were found to be unaltered and showed the potent clastogenic nature of plant extract. As concentrations of plant extract and exposure time increase, the frequency of occurrence of cytogenetic aberrations was also detected to be more. Further, the potential genotoxicity of plant measured in terms of mitotic index reduction also confirms its significant role in inducing mutagenicity. The genoprotective efficacy of extract was identified as its ability to inhibit and reverse the aberrations caused by H2O2 at lower concentrations of plant extract. Conclusions: Dose-dependent data highlight the cytotoxic and genoprotective effect of C. latifolia on the A. cepa model. These findings will help to exploit the plant as an anticancer drug and explore other wide arrays of therapeutic activities of C. latifolia.